A REVIEW ON THE ENGINEERING PROPERTIES OF SOYBEAN TO SUPPORT THE TOFU AGRO-INDUSTRIAL MACHINERY DEVELOPMENT AND IMPORTANT HIGHLIGHTS - Agustami Sitorus; Devianti Devianti; Ramayanty Bulan (AGROINTEK, 2021)
The physical and mechanical properties of the material to be processed are fundamental and continue to be a challenge for researchers to design a machine appropriately. Studies of the soybean engineering properties have not been widely highlighted and reviewed. This makes researchers and engineers of soybean processing machines still have to search through experimentation or read deeply through scientific papers before applying it. Therefore, this paper presents highlights and reviews of studies related to the measurement and modelling of soybean engineering properties. The objective is to study methodologies uses and identify future research directions to get a result in more accuracy. Several papers are searched from various search engines for scientific articles that are available online. Some keywords and a combination of keywords used in the search process are “physical properties”, “mechanical properties”, “soybean grains” and “moisture-dependent”. The results show that ten scientific papers are strictly related to the measurement and modelling of the engineering properties of soybean. In general, the documents found were in the period 1993 to 2012. The research paper investigated the engineering properties of soybean in the moisture content ranges from 6.7% (d.b.) to 49.7% (d.b.). The widely studied physical properties are diameter, surface area, roundness, the weight of 1000 soybeans, bulk density, and true density associated with moisture content. Mechanical parameters investigated include friction coefficient, angle of repose, terminal velocity, angle of internal friction, rupture force, and rupture energy. On the one hand, some of the engineering properties of soybeans that have not yet been discovered are thermal, optical, and aerodynamic properties. On the other hand, the effect of soaking and blanching on changes in the engineering properties of soybean (physical, mechanical, thermal, optical, and aerodynamic) has not been done in-depth. Besides that, most of the soybean processing agro-industry requires engineering properties of soybean to be able to design their machines more precisely. One of the agro-industries that need data on the study results of the nature of engineering with these treatments is the tofu processing industry.